Chemical compounds related to nutraceutical and industrial qualities of non‐transgenic soybean genotypes - Carrera, Constanza Soledad; Dardanelli, Julio Luis; Soldini, Diego Omar (Wiley; Society of Chemical Industry, 2019)
BACKGROUND: Information about the chemical profile of soybean seed is valuable for breeding programs aimed at obtaining value‐added products to meet the demands of niche markets. The objective of this study was to determine seed composition of non‐transgenic soybean genotypes with specialty characters in different environments of Argentina. RESULTS: Protein and oil contents ranged from 396 to 424 g kg−1 and from 210 to 226 g kg−1, respectively. Oleic and linolenic acid ratio, the general indicator of oil quality, varied from 2.7 to 3.8. The oil contained high levels of total tocopherols (1429–1558 mg kg−1) and the meal exhibited high levels of total isoflavones (2.91–4.62 mg g−1). The biplot showed that oleic, linoleic and linolenic acids, γ‐, δ‐ and total tocopherols, genistin, malonyl daidzin and genistin, acetyl daidzin and glycitin and total isoflavones allowed the greatest discrimination among the genotypes studied. CONCLUSION: Different chemical profiles of each non‐transgenic genotype analyzed were established and, therefore, their identity was defined. These results are important for breeders who intend to obtain new genotypes with improved meal and oil quality, as well as for processors and exporters, who could use them directly as raw material for soyfood processing for nutraceutical purposes